Probabilistic degenerate central Bell polynomials - Li Chen; Taekyun Kim; Dae San Kim; Hyunseok Lee; Si-Hyeon Lee (Mathematical and Computer Modelling of Dynamical Systems)
Assume that [Formula: see text] is a random variable whose moment generating function exists in a neighbourhood of the origin. In this paper, we study the probabilistic degenerate central Bell polynomials associated with [Formula: see text], as probabilistic extension of the degenerate central Bell polynomials. In addition, we investigate the probabilistic degenerate central factorial numbers of the second kind associated with [Formula: see text] and the probabilistic degenerate central Fubini polynomials associated with [Formula: see text]. The aim of this paper is to derive some properties, explicit expressions, certain identities and recurrence relations for those polynomials and numbers.